2008
DOI: 10.3402/fnr.v52i0.1811
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols/stanols as cholesterol lowering agents: a meta-analysis of randomized controlled trials

Abstract: Background: Consumption of plant sterols has been reported to reduce low density lipoprotein (LDL) cholesterol concentrations by 5Á15%. Factors that affect plant sterol efficacy are still to be determined. Objectives: To more precisely quantify the effect of plant sterol enriched products on LDL cholesterol concentrations than what is reported previously, and to identify and quantify the effects of subjects' characteristics, food carrier, frequency and time of intake on efficacy of plant sterols as cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
190
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(201 citation statements)
references
References 83 publications
4
190
1
6
Order By: Relevance
“…Many chemical compounds derived from natural foods have been reported to exert strong biological activity against T2DM [30,31]. Among of them, plant sterols and stanols have drawn particular attention due to their wide distribution in food plants and potent ability to reduce blood fat content [12]. In the present study, we mainly investigated the effects of SMR, which is one kind of plant sterol involved in T2DM, and its possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many chemical compounds derived from natural foods have been reported to exert strong biological activity against T2DM [30,31]. Among of them, plant sterols and stanols have drawn particular attention due to their wide distribution in food plants and potent ability to reduce blood fat content [12]. In the present study, we mainly investigated the effects of SMR, which is one kind of plant sterol involved in T2DM, and its possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterol is a bioactive natural product present in plants that has a structure similar to cholesterol, has no influence on human cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C), and increases the ratio of HDL-C/LDL-C and HDL-C/TC in blood [12]. As a member of the phytosterol family, stigmasterol (SMR) (Figure 1(a)) is widely present in plant oil and plant-based foods, such as soybean, corn, peanut, and sunflower oils [13].…”
Section: Introductionmentioning
confidence: 99%
“…A similar health claim also exists in the USA (28) . Evidence from two early analyses (29,30) and two more recent meta-analyses (31,32) were cited in support of the claim. In brief, the more recent analyses involved pooling of data from a large number of RCT, either eighty-four trials including 141 trial arms (6805 subjects) (31) , or fiftynine RCT (n .…”
Section: Plant Stanols and Sterolsmentioning
confidence: 99%
“…In brief, the more recent analyses involved pooling of data from a large number of RCT, either eighty-four trials including 141 trial arms (6805 subjects) (31) , or fiftynine RCT (n . 4500 subjects) (32) . A non-linear equation comprising two parameters (the maximal LDL-cholesterol lowering and an incremental dose step) was used to describe the dose-response curve, and the overall pooled absolute (mmol/l) and relative (%) LDL-cholesterol-lowering effects of phytosterols were also assessed with a random-effects model (31) .…”
Section: Plant Stanols and Sterolsmentioning
confidence: 99%
“…However, two recent meta-analyses evaluated the LDL-cholesterol-lowering effects of plant sterols and/or stanols. Both found that LDL-cholesterol reduction was approximately 0·33 mmol/l for a mean daily intake of 2·1-2·5 g plant sterols and/or stanols (23,24) . Plant sterols and stanols have approved health claims in the USA and in Europe.…”
Section: Mechanism Of Supporting Statin Therapymentioning
confidence: 99%